Sympathetic Denervation Ameliorates Renal Fibrosis via Inhibition of Cellular Senescence - Li, Qian; Deng, Yuanjun; Liu, Lele; Zhang, Chunjiang; Cai, Yang; Zhang, Tianjing; Han, Min; Xu, Gang (Frontiers in Immunology, 2022)
Objective Continuous over-activation of the renal sympathetic nerve is considered to be an important cause of renal fibrosis. Accumulated senescent cells in the damaged kidney have metabolic activities and secret amounts of proinflammatory factors as part of the SASP (the senescence-associated secretory phenotype), which induce chronic inflammation and fibrosis. It is still unclear whether renal sympathetic nerves affect renal inflammation and fibrosis by regulating cellular senescence. Therefore, we hypothesize that sympathetic activation in the injured kidney induces cellular senescence, which contributes to progressive renal inflammation and fibrosis. Methods Renal denervation was performed 2 days before the UUO (unilateral ureteral obstruction) and UIRI (unilateral ischemia-reperfusion injury) models. The effects of renal denervation on renal fibrosis and cellular senescence were observed. In vitro, cellular senescence was induced in renal proximal tubular epithelial cell lines (TKPTS cells) by treatment with norepinephrine (NE). The selective α2A-adrenergic receptors (α2A-AR) antagonist BRL44408 and β-arrestin2 siRNA, were administered to inhibit NE-induced cellular senescence. Significantly altered pathway was identified through immunoblotting, immunofluorescence, immunocytochemistry, and functional assays involved mitochondrial function. Results Renal fibrosis and cellular senescence were significantly increased in UUO and UIRI models, which were partially reversed by renal denervation. In vitro, NE induced epithelial cells secreting proinflammatory cytokines and promoted cells senescence by activating α2A-AR. Importantly, the effects of NE during cellular senescence were blocked by α2A-AR selective antagonist and β-arrestin2 (downstream of α2A-AR) siRNA. Conclusion Renal sympathetic activation and cellular senescence are important neurometabolic and neuroimmune mechanisms in the development of renal fibrosis. Renal sympathetic neurotransmitter NE acting on α2A-AR of epithelial cells promotes cellular senescence through the downstream β-arrestin2 signaling, which is a potential preventive target for renal fibrosis.